Improved highly efficient Dion–Jacobson type perovskite light-emitting diodes by effective surface polarization architecture. Issue 13 (21st March 2022) - Yang, Hanjun; Tang, Jun; Deng, Liangliang; Liu, Zhe; Yang, Xia; Huang, Zengqi; Yu, Haomiao; Wang, Kai; Li, Jinpeng
Abstract : An effective polarized interface is built by combining the excessive-salt-assisted and antisolvent methods. This cooperation can decrease the trap density and hole injection barrier for high performance DJ-type perovskite light-emitting diodes. Abstract : Quasi-two-dimensional (quasi-2D) perovskites are emerging as promising materials for highly stable light-emitting diodes (LEDs). However, their lower charge transport mobilities and higher defect densities may constrain their light-emitting efficiency. Here, we combine an excessive-salt-assisted (ESA) process with antisolvent treatments to inhibit the defects in Dion–Jacobson-type perovskite LEDs. Such a method could improve the film quality and recombination efficiency. By further investigation, we found that artificially building a bulk junction interface and enhancing surface polarization could play a more important role in promoting the ability of charge carrier injection and recombination for high-performance LED devices. Accordingly, the DJ-type quasi-2D perovskite LED can achieve a high external quantum efficiency (EQE) of 7.1%.